(3GdaSQ aj TQM OjhGf GdeJfHis - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s ((3eMeO Hf CMeO Hf YHOGdedc, bhGe GdaGQGHj GdCJbGfj s)
(3ChdgG (B:s
(3SCdJ, GOGe Gddg JSOjOc Cf CUfY dc TYQ CHj GdWjH CMeO Hf GdMSjf GdeJfHj jaSQ eYGfjg, hGjQGO GdCTjGA ajg s
(3BNQgG (B:s
(3MJi ChMSfhg efg aGYJbdg hVjb Ydjg acJH Edjg jeOMg(B: (3CjG NqQQ Gddog hQO GdNOhO s
(3GdTGYQ gh GHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHOGdUeO GdLYaj Gdchaj GdcfOj GdeYQha HCHj GdWjH GdeJfHj hGdeJhai(B354s
(3HGdeYgO fSNI CNQi HYfhGf(B: (3TQM OjhGf GdeJfHj dGHf Lqfjs
(3GfXQ GdbSe GdQGHY ef GdLRA GdChd aj GdCOH CQbGes
(3cJHgG fGSNGf s
(3eQJH Ydi GdbhGaj s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs